Transformasi PPL-KKN Integratif Menjadi Program Latihan Profesi di Prodi Manajemen Pendidikan Islam - Misbah Ulmunir (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
The implementation of Presidential Decree number 8 year 2012 about Indonesian National Qualification Framework (KKNI) and Act number 14 year 2005 about teacher and lecturer, requires reorganization and qualification development of the higher education institution which run a program for education and administratif staf education (LPTK) as well as all instruments within it. Course changing as an academic effort in the education institution should be designed sistematically by considering the constitution as well as to accomdate the needs. This research is a qualitatif research using careful tracing toward various documents related to the transformation of the course Integrative Teaching Experience and Community Service (PPL KKN) into Internship II in the Faculty of Tarbiyah and education, as well as interview, documentation, and observation to the transformation process. Researcher used triangulation technique to check the data validity. The research shows that the transformation of course Integrative Teaching Experience and Community Service (PPL-KKN) into PLP II covers the vision and mision, aim, advantage, outline changes, organiser, implementation mechanism, and evaluation.